STUDI EVALUASI IMPLEMENTASI KURIKULUM MERDEKA UNTUK PENGUATAN LITERASI BAHASA INDONESIA DI SDN 004 SALO - Rizki Ananda; Krisdayanti, Leli; Dwi Nafiun Nurul Putri; Bunga Chantika; Alis Permita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Kurikulum Merdeka was introduced as a response to the need for a more contextual and student-centered education system, including the reinforcement of Indonesian language literacy at the elementary school level. This study aims to evaluate the implementation of the Kurikulum Merdeka in strengthening Indonesian language literacy at SDN 004 Salo and to identify its supporting and inhibiting factors. The research employed a qualitative method with a descriptive evaluative approach based on the CIPP model (Context, Input, Process, Product). Data were collected through participatory observation, in-depth interviews with the principal, teachers, students, and parents, as well as document analysis, including lesson plans (RPP) and curriculum reports. The findings indicate a clear need for literacy enhancement, yet the readiness of teachers and the availability of supporting facilities remain limited. The learning process has started to adopt Kurikulum Merdeka strategies; however, the implementation is still inconsistent. Overall, there has been an improvement in students’ literacy skills, particularly in reading and writing, although it is not evenly distributed. Internal factors such as school leadership and teacher enthusiasm serve as strengths, while external factors such as limited resources and low parental involvement remain challenges. This study concludes that the Kurikulum Merdeka has significant potential to improve student literacy if supported by adequate training, facilities, and collaboration.